‘Everyone has their reasons for curating the data they have decided to keep’: a thematic analysis of data hoarding as digital curation practice - Emily Maemura; Travis L. Wagner (Information Research: An International Electronic Journal)
Introduction. This paper presents a preliminary analysis of the r/DataHoarder subreddit, an online community focused on social, legal, and technical practices related to digital curation. We contrast how they conceptualize their practices with the models, frameworks, and capabilities established for digital curation in more traditional memory institutions.